2009
DOI: 10.4161/cc.8.4.7752
|View full text |Cite
|
Sign up to set email alerts
|

PPARδ agonist-mediated ROS stimulates mouse embryonic stem cell proliferation through cooperation of p38 MAPK and Wnt/β-catenin

Abstract: N O T D I S T R I B U T E .PPARδ (peroxisome proliferator-activated receptor delta) is a member of the nuclear receptor superfamily. However, its function in tissues and cells is unknown, particularly as related to stem cell biology. We therefore investigated the PPARδ effects on DNA synthesis in mouse embryonic stem cells (ES cells) and its related signal pathways. PPARδ increased biphasic reactive oxygen species (ROS) production at 15 min and at 120 min incubation. PPARδ significantly increased [ 3 H] thymid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 43 publications
(59 reference statements)
0
18
0
Order By: Relevance
“…In the past several years, the cross-talk between the p38/MAPK and the Wnt/b-catenin signalling pathways have been noticed [28][29][30] with little mechanistic explanation. In this study, we show for the first time that the MAPK/p38/Ap-1 signalling pathway is coupled with the Wnt/b-catenin signalling via the REGg proteasome system, promoting skin tumour development.…”
Section: Discussionmentioning
confidence: 99%
“…In the past several years, the cross-talk between the p38/MAPK and the Wnt/b-catenin signalling pathways have been noticed [28][29][30] with little mechanistic explanation. In this study, we show for the first time that the MAPK/p38/Ap-1 signalling pathway is coupled with the Wnt/b-catenin signalling via the REGg proteasome system, promoting skin tumour development.…”
Section: Discussionmentioning
confidence: 99%
“…Many results have shown that substantial crosstalk can be found during formation and development of tumors between the 'Wnt signaling pathway' and the 'MAPK signaling pathway'. When the 'Wnt signaling pathway' or the 'MAPK signaling pathway' becomes disordered, abnormal embryonic development, defects or even early premature death may occur, and this may lead to loss of control in cell proliferation and differentiation, and further induce tumors (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
“…6 Our findings are consistent with the low expression levels of PGC1α in colon cancers, 6,33 as well as with the decrease of PGC1α linked to the variation of peroxisome proliferator-activated receptor gamma (PPARγ) expression level as, for instance, in human breast cancer. [33][34][35][36] On the contrary the overexpression of PGC1α in intestinal cells determines the increase of PPARγ target genes. 6 Importantly, PPARγ signaling exacerbates colon cancer development 37,38 even if, on the other marked COX activity increase in both HCT116 Bax +/-and Bax …”
Section: ©2 0 1 1 L a N D E S B I O S C I E N C E D O N O T D I S Tmentioning
confidence: 99%
“…36 The cells were maintained in Dulbecco's modified Eagle's medium supplemented with 10% FBS and 1% penicillin/streptomycin. Human PGC1α adenovirus (hAdPGC1α) was generated as described before in reference 6.…”
Section: Cell Cultures and Adenoviral Infection Hct116 Baxmentioning
confidence: 99%